Biochemical and insecticidal efficacy of clove and basil essential oils and two photosensitizers and their combinations on Aphis gossypii glover (Hemiptera: Aphididae) (Bioscience Journal, 2023)
The present study investigates the insecticidal and biochemical effects of two essential oils (EOs) and two photosensitizers against cotton aphids in a laboratory setting. The EOs evaluated were clove (Syzygium aromaticum L.) and basil (Ocimum basilicum), while the photosensitizers were rose bengal and rhodamine B. The individual median lethal concentrations (LC50) revealed that clove was ~4.44 times more potent than basil, and rhodamine B was ~1.34 times more potent than rose bengal. The mortality rates increased using higher concentrations of the photosensitizers and prolonging exposure time to sunlight. The most effective combination against adult aphids was found to be a mixture of sub-lethal concentrations of clove and rhodamine B, resulting in a mortality rate of 92.31%. Conversely, the combination of basil and rose bengal exhibited the lowest efficacy with a mortality rate of 33.33%. Biochemical analyses indicate that Rhodamine B, basil, and the basil-rhodamine B mixture (mixture C) significantly reduced trehalase activity. However, the protease activity significantly increased in aphids treated with rose bengal, clove, and the clove-rose bengal mixtures (mixtures A and B). The lipase activity is notably decreased upon treatment with rhodamine B and clove. Glutathione S-transferase (GST) activity decreased in aphids treated with rose bengal and the basil-rhodamine B mixtures (mixtures C and D), suggesting that GST did not play a role in detoxifying these compounds, thereby explaining the susceptibility of A. gossypii. Overall, the combination of essential oils and photosensitizers has demonstrated a synergistic effect in controlling Aphis gossypii, offering great potential as an effective strategy for aphid management.